Ethnoculture and Economics: A Synergy of Possibilities. Issue 1 (4th May 2021) - Popkov, Iu.V.; Tiugashev, E.A.
ABSTRACT: This article surveys the conceptual assumptions behind research into the connection between ethnocultural diversity and the social mechanisms of economic life. It identifies ideas from the classics of political economy on this particular topic with special emphasis on the nation-centric, which documents the decisive impact of climate conditions, type of economy, cultural specifics, and unique features of the national character on the economic specialization of nations. It considers ethnocultural diversity as an additional economic resource. It identifies ecological–economic ideas about the stability and productivity of ecological communities, which it uses to interpret the role of ethnocultural diversity in the socioeconomic development of interethnic communities and in ensuring their social stability and economic productivity. By analyzing a geographically localized economy as an interethnic community, it draws conclusions about the beneficial effects of ethnocultural diversity on economic development and interethnic relations, provided that foreign ethnocultural groups are successfully integrated into the host community.